Bombshell [videorecording (DVD)] - Theron, Charlize; Kidman, Nicole, 1967-; Lithgow, John, 1945-; McDowell, Malcolm, 1943-; Janney, Allison; Robbie, Margot, 1990-; McKinnon, Kate, 1984-; Britton, Connie (Lionsgate, 2020)
A group of women decides to take on Fox News head Roger Ailes and the toxic atmosphere he presided over at the network.